Immune and Safety Analysis of ultraIPVTM, a Novel UVC-Inactivated Polio Vaccine - David A. MacLeod; John K. Tobin; Ruth V. Bushnell; Taralyn J. Wiggins; Shyamkumar TS; Ramchander Nadipelly; Steven Lawson; Viju V. Pillai; Gregory J. Tobin; Stephen J. Dollery (Viruses)
The eradication of poliovirus remains a global health priority, with inactivated polio vaccines (IPVs) playing a pivotal role in immunization strategies. Over the past decades, advancements in IPV production have focused on optimizing safety, efficacy, and immunogenicity while addressing vaccine production and logistical challenges. This paper discusses a novel IPV candidate, ultraIPVTM, which departs from conventional formalin inactivation and uses a modern ultraviolet C (UVC) inactivation technology that includes a powerful antioxidant that protects virus epitopes from damage during and after irradiation. The potential of UVC inactivation to maintain structural integrity and immunogenicity of viral antigens, while circumventing safety issues with conventional vaccines, could bolster global polio eradication efforts and holds promise for applications to numerous other viral pathogens. Wistar rats were immunized with three dosages of ultraIPVTM, IPOLR, or vehicle alone. Immune responses were analyzed by whole-virus ELISA and antiviral neutralizing responses. Toxicity was analyzed primarily by increases in body weight and cytokine ELISA. Tolerability was analyzed by gross pathological and histological examinations. ultraIPVTM was determined to be immunogenic and non-toxic. No pathological or histological abnormalities related to the vaccine were observed. The data suggest that ultraIPVTM is immunogenic and well-tolerated in rats.